Formulasi Sediaan Balsam Ekstrak Rimpang Jahe Putih (Zingiber officinale) dengan Variasi Konsentrasi Cera Alba sebagai Stabilizing Agent - Unique, I Gusti Ayu Nadia Prasta; Tiari, Ida Ayu Putu Murnita; Buana, Komang Dirga Mega (Jurnal Ilmiah Medicamento, 2024)
Balm is a semi-solid topical preparation that provides a warming sensation. Cera alba is commonly used as a stabilizing agent at 5% to 20% concentrations. This study aimed to evaluate the effect of varying concentrations of Cera alba on the physical stability of a balm containing white ginger (Zingiber officinale) rhizome extract. The balm was formulated with 5% white ginger rhizome extract and varying concentrations of Cera alba at 5%, 15%, and 20%. Stability testing was performed using the cycling test method, including organoleptic properties, pH, homogeneity, adhesion, and spreadability assessments. The results showed that all formulations exhibited good organoleptic characteristics and homogeneity without significant changes. An increase in pH and adhesion was observed in all formulations, although they remained within acceptable limits. However, the F0 (base only), F1, and F3 formulations demonstrated an increase in spreadability that did not meet the required criteria, while only the F2 formulation containing 15% Cera alba fulfilled all physical stability requirements before and after the cycling test. A 15% Cera alba concentration was identified as the optimal concentration to produce a stable balm that meets the required standards. These findings contribute to developing more effective and high-quality topical preparations and provide a valuable reference for the pharmaceutical industry in selecting the optimal composition for herbal-based balm products with Cera alba as a stabilizing agent.